Angiotensin II Type I Receptor Antagonism Attenuates Nicotine-Induced Cardiac Remodeling, Dysfunction, and Aggravation of Myocardial Ischemia-Reperfusion Injury in Rats - Ramalingam, Anand; Budin, Siti Balkis; Mohd. Fauzi, Norsyahida; Ritchie, Rebecca H.; Zainalabidin, Satirah (Frontiers in Pharmacology, 2019)
Increased exposure to nicotine contributes to the development of cardiac dysfunction by promoting oxidative stress, fibrosis, and inflammation. These deleterious events altogether render cardiac myocytes more susceptible to acute cardiac insults such as ischemia-reperfusion (I/R) injury. This study sought to elucidate the role of angiotensin II type I (AT1) receptors in cardiac injury resulting from prolonged nicotine administration in a rat model. Male Sprague-Dawley rats were given nicotine (0.6 mg/kg ip) for 28 days to induce cardiac dysfunction, alone or in combination with the AT1 receptor antagonist, irbesartan (10 mg/kg, po). Vehicle-treated rats were used as controls. Rat hearts isolated from each experimental group at study endpoint were examined for changes in function, histology, gene expression, and susceptibility against acute I/R injury determined ex vivo. Rats administered nicotine alone exhibited significantly increased cardiac expression of angiotensin II and angiotensin-converting enzyme (ACE) in addition to elevated systolic blood pressure (SBP) and heart rate. Furthermore, nicotine administration markedly reduced left ventricular (LV) performance with concomitant increases in myocardial oxidative stress, fibrosis, and inflammation. Concomitant treatment with irbesartan attenuated these effects, lowering blood pressure, heart rate, oxidative stress, and expression of fibrotic and inflammatory genes. Importantly, the irbesartan-treated group also manifested reduced susceptibility to I/R injury ex vivo. These findings suggest that AT1 receptors play an important role in nicotine-induced cardiac dysfunction, and pharmacological approaches targeting cardiac AT1 receptors may thus benefit patients with sustained exposure to nicotine.